2015
DOI: 10.3341/kjo.2015.29.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watching 3-Dimensional Television on Refractive Error in Children

Abstract: PurposeTo investigate the effect of watching 3-dimensional (3D) television (TV) on refractive error in children.MethodsSixty healthy volunteers, aged 6 to 12 years, without any ocular abnormalities other than refractive error were recruited for this study. They watched 3D TV for 50 minutes at a viewing distance of 2.8 meters. The image disparity of the 3D contents was from -1 to 1 degree. Refractive errors were measured both before and immediately after watching TV and were rechecked after a 10-minute rest per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The association of refractive error with parent's level of education has been found elsewhere 3 . With advancement in technology, extensive use electronic gadgets and lack of outdoor activities by pupils from medium to high income homes could result in high prevalence of myopia and an increase in the number of avoidable blindness due to refractive error [31][32][33][34]. Genetic and ethnic factors may also play a role [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The association of refractive error with parent's level of education has been found elsewhere 3 . With advancement in technology, extensive use electronic gadgets and lack of outdoor activities by pupils from medium to high income homes could result in high prevalence of myopia and an increase in the number of avoidable blindness due to refractive error [31][32][33][34]. Genetic and ethnic factors may also play a role [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, continuous use for > 30 min is discouraged, although these warnings are based on weak evidence [1]. Many studies have reported that a signi cant proportion of VR device users experience a highly aversive sense of discomfort, disorientation, nausea, and motion sickness, and these reports suggest that viewing stereoscopic images on 3D devices may induce visual asthenopia, such as visual discomfort and fatigue [2][3][4][5][6]. It is essential to study the effects of VR devices on the eye, as HMD images are presented to users at a short distance with a powerful convex lens to simulate 3D reality.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Interestingly, Suh et al reported that watching 3D videos can lead to transient myopia. 10 Presently, the effects of VR device use on vision are not clear, and it is unknown whether a specially designed VR training device can eliminate visual fatigue and improve myopia.…”
Section: Introductionmentioning
confidence: 99%